1D hollow α-Fe2O3 electrospun nanofibers as high performance anode material for lithium ion batteries - Chaudhari, Sudeshna (2013)
Hollow-structured α-Fe2O3 nanofibers were successfully synthesized by a simple electrospinning technique using iron acetylacetonate (Fe(acac3)) and polyvinylpyrrolidone (PVP) precursor. Fe (acac)3–PVP composite fibers were calcined at high temperature to form an interconnected 1D hollow-structure of α-Fe2O3 nanofibers. Thermogravimetric analysis (TGA), X-ray diffraction (XRD), field-emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM) and Brunauer–Emmett–Teller (BET) were employed to characterize α-Fe2O3 hollow fibers. Based on the characterization results, a formation mechanism for electrospun α-Fe2O3 hollow fibers is proposed. Electrochemical measurements showed that the hollow-structure of α-Fe2O3 nanofibers played an important role in improving the electrode cycle stability and rate capability in lithium ion batteries. The α-Fe2O3 hollow fiber anodes exhibit a high reversible capacity of 1293 mA h g−1 at a current density of 60 mA g−1 (0.06 C) with excellent cycle stability and rate capability. Based on our study this high performance is attributed to the interconnected hollow-structure of large aspect ratio α-Fe2O3 nanofibers, which makes them a potential candidate for lithium ion batteries.